Evaluasi Kepemimpinan Transformasional Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan dengan Menggunakan Model CIPP - Yoseb Sudarso Bunbaban; Ade Iriani; Marinu Waruwu (Universitas Kristen Satya Wacana, 2022)
The low quality of education has an impact on the future of every student. Therefore, the quality of education is very important for everyone who wants to achieve a hope and future and has the ability to compete with others. To achieve this, professional leaders are needed in the field of school leadership. Leadership is the strength and readiness of a person to be able to influence, motivate, embrace, move, and if necessary force other people so that people accept the influence that is carried out so as to shape the process of achieving the goals that have been set. the emergence of transformational leaders can change the paradigm of thinking so that every activity can be carried out together to improve the quality of education in accordance with the goals, vision, and mission of the school. Researchers try to position the advantages of the school principal's transformational leadership model in improving the quality of education. Transformational leadership is one of the right choices for school principals as leaders in implementing all their capabilities in improving the quality of education on an ongoing basis so that they can be used as role models for other school principals. The data analysis technique used by researchers in this study used qualitative descriptive data with assessments carried out through observation, interviews, and documentation, then source triangulation was carried out to test the validity of the data obtained about transformational leadership in improving the quality of education. based on the results of research through interviews with the principal, six teachers, the education office, and the Deputy Regent it was concluded that the implementation of the transformational leadership model with visionary characteristics, motivation, stimulus, and individual considerations can improve teacher performance through training, workshops, seminars and holding individual and group meetings with school principals so as to improve the quality of education